El microcrédito de la Cooperativa María Inmaculada otorgado a los usuarios del sistema de riego Chambo-Guano y los efectos en la productividad. - Lizbeth Rosmary, Pillasagua Fajardo (2020)
This research is intended to study the microcredit of the María Inmaculada Savings and Credit Cooperative and the effects on productivity by focusing on the behavior it generates in the users of the Chambo-Guano Irrigation System who have been granted a microcredit. The research carried out is divided into the following chapters: Chapter I: Includes preliminary aspects, the most relevant being the problem statement and objetives, giving the reader the reason for the study. Chapter II: Deals with essential aspects of the state of the art being fundamental variables for the study, citing several investigating autors who give relevance and understanding through enriched contributions, highlighting the most important for their compression. Chapter III: It aboard the methodology detailing the precise tools, using the deductive method, emphasizing the conduct of the serveys, the information was processed, analyzed, and interpreted to later combine data through statistical systems determining the results of the investigation. Finally, the last two chapters, the results obtained are issued determining the conclusions and recommendations, developing the objectives at the beginning of the study.